2010
DOI: 10.1155/2010/824813
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soy Lecithin Administration on Hypercholesterolemia

Abstract: Recent studies suggest that lecithin-rich diet can modify cholesterol homeostasis and hepatic lipoprotein metabolism. Considering the phytotherapeutic impact of lecithin, this work hypothesizes that lecithin administration in hypercholesterolemic patients may reduce cholesterol concentrations by increasing biliary secretion. Total cholesterol and LDL were evaluated after soy lecithin administration in hypercholesterolemic patients. One soy lecithin capsule (500 mg/RP-Sherer) was administrated daily. One-two mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 30 publications
0
23
0
1
Order By: Relevance
“…Soy lecithin decreased the total cholesterol (-7.51%) and the fraction LDL (-26.24%), but increased the fraction HDL (+33.93%). Some researchers showed that a diet containing lecithin modifies the cholesterol homeostasis in the liver, reducing the excess LDL, and promoting the synthesis of a great amount of HDL in the liver (Mourad et al, 2010). There is also an inhibition of the acyl-CoA cholesterol acyltransferase (ACAT) by the SL consumption, and lower ACAT activity was associated with lower, free, and esterified cholesterol content, which may be rapidly directed to the elimination in the bile, or may be converted into biliar acids (LeBlanc et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soy lecithin decreased the total cholesterol (-7.51%) and the fraction LDL (-26.24%), but increased the fraction HDL (+33.93%). Some researchers showed that a diet containing lecithin modifies the cholesterol homeostasis in the liver, reducing the excess LDL, and promoting the synthesis of a great amount of HDL in the liver (Mourad et al, 2010). There is also an inhibition of the acyl-CoA cholesterol acyltransferase (ACAT) by the SL consumption, and lower ACAT activity was associated with lower, free, and esterified cholesterol content, which may be rapidly directed to the elimination in the bile, or may be converted into biliar acids (LeBlanc et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Diets supplemented with SL may result in lower levels of total cholesterol (Attia & Kamel, 2012) and of low-density lipoprotein-cholesterol (LDL-cholesterol) (Mourad et al, 2010). According to LeBlanc et al…”
Section: Introductionmentioning
confidence: 99%
“…22 FDA and German Cancer Research Centre, Heidelberg stated that Soy phosphatidylcholine has no carcinogenicity and no risk in formation of tumour. 23,24 Additionally, PC is said to have varied advanced beneficial properties like hepatoprotective activity, 25 nutritional supplement to support brain health, 26 role in membrane fluidity, 27 shows superior host defences (like enhancing NK cell activity and phagocytosis), 28 excellent emulsifying activity, 29 major component of the gastric mucosa lining of the stomach protecting from ulcer, 30 precursor for acetylcholine, 31 reducing serum cholesterol, 32 improving the perception of taste and smell, 33 recuperate fatigue 34 and even in nourishing skin. 35 …”
Section: Phospholipid Source and Its Additional Benefits As Adjuvantmentioning
confidence: 99%
“…It is available from sources such as soybeans, eggs, milk, cottonseed, and sunflower. Researches indicated that lecithin increase good cholesterol and decrease bad ones [10], [11]. Miranda et al, [12] found that daily lecithin supplementation increased macrophage activity which can engulf cancerous cells in the body by 29% on rats that suggest increase the immune function.…”
Section: Introductionmentioning
confidence: 99%